In vitro rumen fermentability kinetics of parboiled rice bran - Fidriyanto, R.; Ridwan, R.; Rohmatussolihat, R.; Astuti, W. D.; Sari, N. F.; Adi, E. B. M.; Mulyaningsih, E. S.; Widyastuti, Y. (Diponegoro University, 2019)
Parboiled rice product has been widely produced by industry in the developing countries. The increasing of parboiled rice product will consequently increased rice bran waste. Therefore, the objective of the study was to analyze the effect of parboiling processes on nutritional value of rice bran and evaluate nutritional value of parboiled rice bran in the rumen fermentation using in vitro digestibility method. The experiment was arranged in completely randomized factorial design with 2 factors and 3 replications. The first factor is types of rice bran from different rice plant variety consisted of LIPI GO1, LIPI GO2, LIPI GO4, and Sintanur. The second factor is soaking time consist of 0 minute (control), 30 minutes and 60 minutes. Data were analyzed by using ANOVA and significant effects of each treatment were further analyzed by using the least significant difference by Duncan multiple range test (P<0.05). Kinetic parameters of Ørskov’s equation were obtained by non-linear regression procedure. Results showed that the quality of parboiled rice bran was significantly affected by the parboiling process such as soaking periods and rice variety. Chemical composition, rumen gas production, and digestibility of rice bran differ depends on rice variety. Soaking for 30 minutes and 60 minutes decreased organic matter, crude protein, and increased crude fiber (P<0.05). Moreover, soaking rice grain for 60 minutes increased crude fat. The longer of soaking periods decreased of total gas, potential gas production, gas production rate and total organic matter digestibility (P<0.05).